Sunday
March 26, 2017

Post a New Question

Posted by on .

9x+3(x-4)=10(x-5)+7

9x+3x-12=10x-50+7
12x-12=10x-43
subtract -12 from both sides and that leaves
-12=-2x-43
add 43 to both sides and that leaves 31=2x
then the answer is x=31/2 (a fraction)
im so confused and its even harder trying to type it out and not confuse anyone reading it. lol

  • math 012 double check me please - ,

    Your first two steps are fine. On the third, in which you go from

    12x - 12 = 10x - 43

    to

    -12 = -2x - 43

    I think you mean to say you're subtracting 12x from each side.

    Adding 43 to each side leaves 31 = -2x.

    Divide each side by -2 to get x = (-31)/2.

    So, it looks like you were right, except for dropping a - when subtracting 43.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question